Exploring the Process-Based Approach in Academic Writing: English Teachers’ Implementation and Perceived Impact - Gabuay-Vega, Ma. Lovely (Journal of Interdisciplinary Perspectives, 2025)
This study examines the impact of the process-based approach on students' academic writing by exploring how teachers implement this method across different writing stages: pre-writing, drafting, revising, editing, and publishing. Many teachers apply this approach implicitly, and their instructional strategies in each phase influence student progress. The study also investigates teachers' challenges in integrating this model into their writing instruction. Using a qualitative phenomenological design, the research explores the lived experiences of five English teachers from private and public senior high schools in Cavite City. Findings reveal that teachers employ various pedagogical strategies, including idea generation, creative exploration, collaboration, structuring, and revision. However, they encounter challenges such as time constraints, curriculum limitations, student motivation issues, lack of resources, and assessment expectations. Despite these challenges, the process-based approach significantly improves students' writing skills in organization, creativity, language use, critical thinking, and self-reflection. The study recommends adopting this approach more explicitly in writing instruction, encouraging students to actively engage in all writing stages to enhance their writing competency.